The Reflection on Transportation Area of City to Sea and Air Transportation Development in Baubau City - Noor Fadilah Romadhani; M. Yamin Jinca (PINISI Discretion Review, 2023)
Baubau City located in Buton Islands, Province of Southeast Sulawesi, Indonesia, access via sea and air transportation resulting in demand of passengers and goods which reflect on internal movement and transportation service performance. This research aims to analyze reflection on area of city transportation to sea and air transportation development supporting goods and passenger trips and also transportation service performance in Baubau City. Research method is descriptive with qualitative and quantitative analysis through survey such as interview with questionnaires, and secondary data collection from relevant institute. Performance of urban transportation data analysed by using Importance Perfomance Analysis dan Customer Satisfaction Index related to 4 indicators, population trip pattern used origin destination matrix (O-D Matrix) and SWOT and also Quantitative Strategic Planning Matrix (QSPM) analysis to determine reflection on transportation area of city. The research result reveals that the services performance area of city transportation at very poor level, priority handling is regularity indicator. Population trip pattern has not spread evenly, centered on three districts are Murhum, Betoambari and Wolio with total trip of 12,361 person/day. Goods trip pattern only center on Wolio district (port and market area/warehouse). The urgent strategy to be implemented is S-O strategy, which acceleration the ring road development policy to meet development of Baubau East region as well as to optimize the provision of services through mode of water transportation more convenient and secure.